Neoliberal Performans Öznesi ve Stoacı Ruh Dinginliği: Byung-Chul Han ile Seneca Arasında Bir Karşılaşma. - Ekşici, Zeynep (Felsefelogos, 2026)
This study examines the performance-oriented subject that emerges in contemporary neoliberal society within the framework of Byung-Chul Han's critical analyses. It subjects the psychological tension experienced by this subject to an ethical evaluation through Seneca's Stoic conception of tranquillity of the mind. Han argues that, in neoliberal society, the subject experiences itself as a free and autonomous agent; however, this perception of freedom is intertwined with the compulsion to constantly produce performance, to optimize the self, and to engage in self-exploitation. This condition results in psychological pathologies such as fatigue, anxiety, and depression. The study examines Han's diagnosis of these pathologies in relation to the neoliberal subject in detail. The living mode in question is then examined in the following Seneca's ethical criteria. Seneca's conception of the good life, centered on tranquillity of the mind, moderation, and self-mastery, offers a counter-horizon for an ethical evaluation of the lived experience of the neoliberal performance subject. In this context, while the study draws on Han to describe how the contemporary subject functions, it aims, through Seneca, to make visible why this way of life is incompatible with a good life. The aim of the research is not to subject the two thinkers to a historical or doctrinal comparison. Rather, it is to subject the neoliberal performance subject--considered as a single subject on two different planes--to an ethical test. In this way, the study reveals the contemporary critical potential of Stoic ethics in evaluating the psychological pathologies of the neoliberal subject.